OBEDIENCE OF NURSE IN IMPLEMENTING STANDART OPERATING PROCEDURE OF INFUSION INSERTION WITH THE PHLEBITIS - Kurnia, Erlin; Maria, Ince (Jurnal Penelitian STIKES Kediri, 2012)
Phlebitis is veins wall inflammation which usually occurs on intravenous therapy. It happens due to microorganism’s infection of nurses’ hands of during insertion or infusion’s maintenance. To prevent phlebitis, nurses must perform right intravenous infusion on the Infusion’s SOP at Kediri Baptist Hospital. The design used in this research was correlational. The population were all emergency’s patients at Kediri Baptist Hospital who have been done infusion by emergency room’s nurses. Using Purposive Sampling Technique, it was obtained 68 respondents. The independent variable in this study was nurse obedience in implementing Infusion’s SOP (Standard Operating Procedures) while the dependent variable was phlebitis’ incidence. The collected data were analyzed using contingency coefficient test with significance level α ≤ 0.05. The results showed that the implementing of intravenous infusion by the nurses that was obedient were 88,2% and majority of the patients did not happen phlebitis, were 97,1%. The statistical test of Contingency Coefficient result was p = 0.000. In conclusion, there was a relationship between obedience of Emergency Room nurse in implementing Standard Operating Procedure of infusion insertion toward the incidence of phlebitis at Kediri Baptist Hospital.